(untitled) (Altre Modernità, 2019)
No Shoneen: Gaelic Games and the Athletic Hero in the Irish Periodical Press by Elena Ogliari TUTOR: Prof. Paolo Caponi PhD COORDINATOR: Prof. Maria Vittoria Calvi DOCTORAL PROGRAMME in Linguistic, Literary and intercultural Studies in European and Extra-European Perspectives UNIVERSITY: Università degli Studi di Milano ACADEMIC YEAR: 2019